Adenylate cyclase responsiveness to hormones in various portions of the human nephron. - Chabardès, D (1980)
The action sites for parathyroid hormone (PTH), salmon calcitonin (SCT), and arginine-vasopressin (AVP) were investigated along the human nephron by measuring adenylate cyclase activity, using a single tubule in vitro microassay. Well-localized segments of tubule were isolated by microdissection from five human kidneys unsuitable for transplantation. PTH (10 IU/ml) increased adenylate cyclase activity in the convoluted and the straight proximal tubule, in the medullary and cortical portions of the thick ascending limb, and in the early portion of the distal convoluted tubule (corresponding stimulated:basal activity ratios were 64, 19, 10, 18, and 22, respectively). SCT (10 ng/ml) increased adenylate cyclase activity in the medullary and cortical portions of the thick ascending limb, in the early portion of the distal convoluted tubule, and, to a lesser extent, in the cortical and the medullay collecting tubule (activity ratios were 7, 14, 15, 3, and 3, respectively). AVP (1 microM) stimulated adenylate cyclase activity in the terminal nephron segments only, i.e., the late portion of the distal convoluted tubule, the cortical and medullary portions of the collecting tubule (activity ratios 81, 51, and 97, respectively). As measured in one experiment, nearly one-half maximal responses were obtained with 0.1 IU/ml PTH or 0.3 ng/ml SCT in thick ascending limbs and with 1 nM AVP in collecting tubules, suggesting that enzyme sensitivity to hormones as well preserved under the conditions used in this study.